Analysis of Notary Immunity Laws that Open Confidentials in Trial Based on Act No. 2 of 2014 Concerning Amendment to Act No. 30 Of 2004 Concerning Notary Office (Case Study Decision Number 83 / PID.B / 2011 / PN. SKA) - Mahfud Baihaqi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
As a legal instrument, on the one hand the notary has the right to refuse as a professional public official, by having to hold his oath of office not to disclose the contents of the act, on the other hand the notary must stand in the state's interest which refers to the public interest for the settlement process law in Justice, if in the investigation stage up to the hearing of a notary, it is necessary to become a witness in a criminal case, so as to produce a fair decision, useful and guarantee legal certainty. Purpose of research this To Know the Limits of Opening Secrets in a Court based on Invite Number2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Position of Notary Public and To Know the Legal Consequences for Notaries who disclose secrets in court based on Invite Number2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Position of Notary Public. The method used in this research is sociological juridical method, the specification in this research is descriptive analysis, the data used are primary data and secondary data, using data collection by interview and literature study, qualitative data analysis, problems analyzed by theory, law enforcement. And legal certainty. The results of this study indicate that In determining the extent to which the right of denial of the notary public must start from the obligation for the notary not to talk about the contents of his deeds, in the sense of either what is stated in his deeds or about what was notified or conveyed to him in his position as a notary. , even before a court of law, except for matters where there is a higher interest or in matters for which a notary by the applicable laws and regulations expressly exempt him from his oath of secret office. For the purposes of summoning a notary based on Article 66 paragraph 1 letter b. Police, prosecutors and judges must obtain prior permission from the Regional Supervisory Council. On the basis of the request for permission from the Police, the Regional Supervisory Council (MPD) shall hold a panel meeting to examine the notary regarding whether or not the notary is required to provide information at the examination of a criminal case.